Say $n$ can be represented as a sum of three non-zero squares. (i.e. $n = a^2 +b^2+ c^2$, for some $n,a,b,c \in \mathbb{N}$)

Is it possible that every natural power of $n$ is also a sum of three non-zero squares? (i.e. $n^k = x^2+y^2+z^2$ for $x,y,z,k \in \mathbb{N}$)

  • 1
    $\begingroup$ For the second part: it is possible iff you can not write $\;n^k=4^a(8b+7)\;,\;\;a,b\in\Bbb Z\;$ (note that this last is the integers, not merely *the naturals") $\endgroup$ – DonAntonio Mar 6 '18 at 9:51
  • $\begingroup$ Dear David, just a remark. You have accepted an answer where we are also not sure whether the three squares are non-zero. But your claim without this restriction of non-zero follows more easily just by the three-square-theorem. The problem only is "non-zero squares". $\endgroup$ – Dietrich Burde Mar 8 '18 at 10:30

Yes, more generally, if, $$N = x_1^2+x_2^2+\dots+x_m^2$$ then one can always find integer $y_i$ such that, $$N^k = y_1^2+y_2^2+\dots+y_m^2$$

Proof: Use the expansion of


To get,

$$a^2 + w = N,\\ (a^2 - w)^2 + (2 a)^2 w = (a^2 + w)^2,\\ (a^3 - 3 a w)^2 + (3 a^2 - w)^2 w = (a^2 + w)^3,\\ (a^4 - 6 a^2 w + w^2)^2 + (4 a^3 - 4 a w)^2 w = (a^2 + w)^4$$

and so on, then assume $w$ to be a sum of squares $w=b^2+c^2+\dots$

For example, for $k=3$,

$$\small\big(a^3 - 3 a (b^2+c^2+\dots)\big)^2 + \color{blue}{\big(3 a^2 - (b^2+c^2+\dots)\big)^2 \big(b^2+c^2+\dots\big)} = (a^2 + b^2+c^2+\dots)^3$$

then distribute the blue term. I trust the pattern for other $k$ is easy to discern.

  • $\begingroup$ Is it clear that none of the $y_i$ will be zero? $\endgroup$ – Dietrich Burde Mar 6 '18 at 11:41
  • $\begingroup$ @DietrichBurde: Good point. But at least the identity, given initial $k=1$, provides a simple algorithm to generate solutions to $a^2+b^2+c^2 = n^k$ which can then be tested if $abc\neq0$. I'll see if a tweak can address that point. $\endgroup$ – Tito Piezas III Mar 6 '18 at 12:19

Yes, this is possible. Take $n=3$. Clearly $3=1^2+1^2+1^2$. Now any power of $3$ is also the sum of three squares by the Three-Squares Theorem, because $3^k$ is not of the form $4^n(8m+7)$. This may include zero summands, though. Otherwise one has to give a direct solution. If $n=3^k$ with $k=2m+1$, then $3^k=(3^m)^2+(3^m)^2+(3^m)^2$. If $n=3^k$ with $k=2m$, then $$ 3^k=3^{2m}=(3^{m-1})^2+(2\cdot 3^{m-1})^2+(2\cdot 3^{m-1})^2 $$

  • $\begingroup$ Doesn't the three-squares theorem allow $abc=0$ (which the OP here precludes)? $\endgroup$ – Barry Cipra Mar 6 '18 at 10:07
  • $\begingroup$ Yes, good point. Then one needs a direct presentation, i.e., $9=1^2+2^2+2^2$, $27=3^2+3^2+3^2$ and so on. $\endgroup$ – Dietrich Burde Mar 6 '18 at 10:13
  • $\begingroup$ In any event, it seems to me that what the OP really wants is not a single example of an $n$ such that $n^k$ is the sum of three positive squares for all $k$, but a general proof that if $n$ is the sum of three positive squares, then so is $n^k$ for all $k\gt1$. And for that the sum-of-three-squares theorem isn't enough. $\endgroup$ – Barry Cipra Mar 6 '18 at 10:27
  • $\begingroup$ Yes, but this claim may not even be true for all $n$. It certainly is true for single exapmles $n$, like $n=3$. I would now look for a counterexample. $\endgroup$ – Dietrich Burde Mar 6 '18 at 10:31
  • $\begingroup$ In googling on sums of three positive squares, I came across something I'd quite forgotten: mathoverflow.net/questions/90914/sums-of-three-non-zero-squares $\endgroup$ – Barry Cipra Mar 6 '18 at 10:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.